Flame Synthesis of Cu/ZnO-CeO2 Catalysts: Synergistic Metal-Support Interactions Promote CH3OH Selectivity in CO2 Hydrogenation - Zhu, Jiadong; Ciolca, Diana; Liu, Liang; Parastaev, Alexander; Kosinov, Nikolay; Hensen, Emiel J M (ACS catalysis, 2021)
The hydrogenation of CO2 to CH3OH is an important reaction for future renewable energy scenarios. Herein, we compare Cu/ZnO, Cu/CeO2, and Cu/ZnO-CeO2 catalysts prepared by flame spray pyrolysis. The Cu loading and support composition were varied to understand the role of Cu-ZnO and Cu-CeO2 interactions. CeO2 addition improves Cu dispersion with respect to ZnO, owing to stronger Cu-CeO2 interactions. The ternary Cu/ZnO-CeO2 catalysts displayed a substantially higher CH3OH selectivity than binary Cu/CeO2 and Cu/ZnO catalysts. The high CH3OH selectivity in comparison with a commercial Cu-ZnO catalyst is also confirmed for Cu/ZnO-CeO2 catalyst prepared with high Cu loading (∼40 wt %). In situ IR spectroscopy was used to probe metal-support interactions in the reduced catalysts and to gain insight into CO2 hydrogenation over the Cu-Zn-Ce oxide catalysts. The higher CH3OH selectivity can be explained by synergistic Cu-CeO2 and Cu-ZnO interactions. Cu-ZnO interactions promote CO2 hydrogenation to CH3OH by Zn-decorated Cu active sites. Cu-CeO2 interactions inhibit the reverse water-gas shift reaction due to a high formate coverage of Cu and a high rate of hydrogenation of the CO intermediate to CH3OH. These insights emphasize the potential of fine-tuning metal-support interactions to develop improved Cu-based catalysts for CO2 hydrogenation to CH3OH.The hydrogenation of CO2 to CH3OH is an important reaction for future renewable energy scenarios. Herein, we compare Cu/ZnO, Cu/CeO2, and Cu/ZnO-CeO2 catalysts prepared by flame spray pyrolysis. The Cu loading and support composition were varied to understand the role of Cu-ZnO and Cu-CeO2 interactions. CeO2 addition improves Cu dispersion with respect to ZnO, owing to stronger Cu-CeO2 interactions. The ternary Cu/ZnO-CeO2 catalysts displayed a substantially higher CH3OH selectivity than binary Cu/CeO2 and Cu/ZnO catalysts. The high CH3OH selectivity in comparison with a commercial Cu-ZnO catalyst is also confirmed for Cu/ZnO-CeO2 catalyst prepared with high Cu loading (∼40 wt %). In situ IR spectroscopy was used to probe metal-support interactions in the reduced catalysts and to gain insight into CO2 hydrogenation over the Cu-Zn-Ce oxide catalysts. The higher CH3OH selectivity can be explained by synergistic Cu-CeO2 and Cu-ZnO interactions. Cu-ZnO interactions promote CO2 hydrogenation to CH3OH by Zn-decorated Cu active sites. Cu-CeO2 interactions inhibit the reverse water-gas shift reaction due to a high formate coverage of Cu and a high rate of hydrogenation of the CO intermediate to CH3OH. These insights emphasize the potential of fine-tuning metal-support interactions to develop improved Cu-based catalysts for CO2 hydrogenation to CH3OH.